2017
DOI: 10.1007/s00299-017-2134-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SbAP37 in rice alleviates concurrent imposition of combination stresses and modulates different sets of leaf protein profiles

Abstract: SbAP37 transcription factor contributes to a combination of abiotic stresses when applied simultaneously in rice. It modulates a plethora of proteins that might regulate the downstream pathways to impart salt stress tolerance. APETALA type of transcription factor was isolated from Sorghum bicolor (SbAP37), overexpressed in rice using a salt inducible abscisic acid 2 (ABA2) promoter through Agrobacterium tumefaciens following in planta method. Transgenics were confirmed by PCR amplification of SbAP37, hygromyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…By and large, these genes are involved in various stress responses, and their underlying mechanisms are fairly well understood. Several overexpression studies in multiple plants species such as Arabidopsis, rice, and soybean demonstrated the involvement of other TFs such as OsAP21 , SbAP37 , GmDREB6 , and OsMYB6 in salt stress tolerance, and in some cases, it was accompanied by accumulation of proline [ 180 , 181 , 182 , 183 ].…”
Section: Genetic Engineering For Salinity Tolerance In Plantsmentioning
confidence: 99%
“…By and large, these genes are involved in various stress responses, and their underlying mechanisms are fairly well understood. Several overexpression studies in multiple plants species such as Arabidopsis, rice, and soybean demonstrated the involvement of other TFs such as OsAP21 , SbAP37 , GmDREB6 , and OsMYB6 in salt stress tolerance, and in some cases, it was accompanied by accumulation of proline [ 180 , 181 , 182 , 183 ].…”
Section: Genetic Engineering For Salinity Tolerance In Plantsmentioning
confidence: 99%
“…Results of comparative proteomics studies for instance showed that the accumulation of vicilin during the pre-treatment of two defense elicitors β-amino butyric acid and γ-amino butyric acid in citrus seed germination under salt stress conditions reversed salt stress impediment and improved germination vigor (Ziogas et al 2017). Two additional studies unraveled the salt tolerance mechanisms through epigenetics (Pandey et al 2016) and proteomics (Parveda et al 2017).…”
mentioning
confidence: 96%